Knowledge Transfer Programme (KTP) and income potential: food and cultural dimension of western food for school students / Fadzleen Suhaimi ... [et al.] - Suhaimi, Fadzleen; Mohd Fisol, Nur Nadia Maisarah; Bibit, Nur Syahira; Zaeimoedin, Teku Zariff (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
Service Learning Malaysia-University for Society or SULAM is an educational method that enables students the chance to utilize their knowledge, expertise, and abilities in their profession to address problems or concerns in their community. This is one of Malaysia's higher education systems' efforts to create graduates that are whole, balanced, and have an entrepreneurial attitude. SULAM is a component of High Impact Educational Practices, which were included in the academic program's curriculum by the Ministry of Higher Education (MoHE) in 2016 (SULAM, Universiti Teknologi MARA (UiTM), 2020). In addition, SULAM is a course-based, credit-bearing educational experience in which students engage in a structured service activity that addresses identified community needs, reflect on the service activity and experiences to achieve desired learning outcomes, and act in a way that fosters a stronger sense of civic responsibility and personal values (SULAM, Universiti Teknologi MARA (UiTM), 2020).To achieve this academic program curriculum, a program named Knowledge Transfer Programme (KTP) and Income Potential: Food and Cultural Dimension of Western Food for School Students was organised by the course Food and Society (HTC556) taken by Bachelor of Science (Hons.) Culinary Arts Management students. It was held in Sekolah Menengah Kebangsaan Dato Kailan (SMKDK), Kepala Batas, Penang on May 24, 2023, from 7am to 3pm. This programme was attended by 30 UiTM Permatang Pauh students, three assistant lecturers, one guest lecturer from MAHSA University, and 44 students from Program Vokasional Menengah Atas, Kursus Penyediaan & Pembuatan Makanan SKM 2 SMKDK.